Cancer-preventing vaccination programs in prison: promoting health equity in Europe - Cocco, Nicola; Tramonti Fantozzi, Maria Paola; Ihuthia, Josephine Njeri; Moazen, Babak; Meroueh, Fadi; Barbîroș, Irina; Mavrou, Josephina; Bardelli, Angela; De Vita, Erica; Plugge, Emma; Tavoschi, Lara; Ranieri, Roberto; et al. (The lancet. Regional health, 2024)
The most important human oncogenic viruses are hepatitis B virus (HBV) and human papillomavirus (HPV). The roll-out of vaccinations against HPV and HBV is a significant public health initiative with robust evidence of impact on the prevention of infection and neoplastic disease sequelae. Incarcerated individuals frequently have suboptimal immunisation levels for a wide variety of vaccine-preventable diseases, including HBV and HPV, and a high burden of disease for HBV/HPV-related cancers. In this Personal View, we analyse evidence regarding HBV and HPV vaccination in prison settings in 20 European countries and integrate it with existing scientific literature to discuss the rationale and possible strategies to expand cancer-preventing vaccination in prison populations. Enhancing HBV/HPV vaccination offer and uptake of HBV/HPV vaccination for this population would not only contribute to reducing the derived burden among the European population, but would also foster health equity and boost efforts towards the attainment of global and regional public health targets.
Online verfügbar: 19. Juni 2024, Artikelversion: 1. August 2024
Gesehen am 21.07.2025